Why talk is not cheap - Boosting women's agribusinesses through dialogue: results and lessons from Kenya and Vietnam - Hoijtink, Leonie (SNV Netherlands Development Organisation, 2019)
Presented by Leonie Hoijtink (SNV), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.